KEKERASAN SEKSUAL TERHADAP PEREMPUAN DI DAERAH KONFLIK (KAJIAN HUKUM INTERNASIONAL DAN PENERAPANNYA DI INDONESIA) - Veriena J. B. Rehatta (Faculty of Law, Universitas Pattimura, 2014)
armed conflict or war often brings its own problems for women and girls, where women are always used as a means of impingement biological desire of the perpetrators of war. Internationally there are several recorded cases bring the dark history for women, for example Akayesu case, Furundzija case. Partizan cases, Foca-Yugoslavia also to witness how the women were abused her self-esteem. Universal Declaration of Human Rights (UDHR) which is the foundation of all human rights norms are universal, in preamble set recognition of the equality of human dignity. All of it is the foundation of freedom, justice and peace in the world. Article 7 of the Convention rights-civil and political rights states that everyone has the right to freedom from torture, treatment or punishment or Punishment cruel Inhuman and Degrading. Indonesia then ratified through Law No. 5 of 1998 and Act No. 39 of 1999 on Human Rights. By ratifying these provisions, then Indonesia is bound by the legal norms and by itself is a part of national law. based on the law, it is for the completion of each issue of human rights violations established national human rights commission